New benzimidazole derivative compounds with in vitro fasciolicidal properties - Elora Valderas-García; Verónica Castilla-Gómez de Agüero; Laura González del Palacio; Giulio Galli; Nerea Escala; Marta Ruiz-Somacarrera; Marta González-Warleta; Esther del Olmo; Rafael Balaña-Fouce; María Martínez-Valladares (Parasites & Vectors, 2024)
Abstract Background Control of the zoonotic food-borne parasite Fasciola hepatica remains a major challenge in humans and livestock. It is estimated that annual economic losses due to fasciolosis can reach US$3.2 billion in agriculture and livestock. Moreover, the wide distribution of drug-resistant parasite populations and the absence of a vaccine threaten sustainable control, reinforcing the need for novel flukicides. Methods The present work analyses the flukicidal activity of a total of 70 benzimidazole derivatives on different stages of F. hepatica. With the aim to select the most potent ones, and screenings were first performed on eggs at decreasing concentrations ranging from 50 to 5 µM and then on adult worms at 10 µM. Only the most effective compounds were also evaluated using a resistant isolate of the parasite. Results After the first screenings at 50 and 10 µM, four hit compounds (BZD31, BZD46, BZD56, and BZD59) were selected and progressed to the next assays. At 5 µM, all hit compounds showed ovicidal activities higher than 71% on the susceptible isolate, but only BZD31 remained considerably active (53%) when they were tested on an albendazol-resistant isolate, even with values superior to the reference drug, albendazole sulfoxide. On the other hand, BZD59 displayed a high motility inhibition when tested on adult worms from an albendazole-resistant isolate after 72 h of incubation. Conclusions BZD31 and BZD59 compounds could be promising candidates for the development of fasciolicidal compounds or as starting point for the new synthesis of structure-related compounds. Graphical Abstract